A Secure-Coordinated Expansion Planning of Generation and Transmission Using Game Theory and Minimum Singular Value - Mehdi Zareian Jahromi; Mohsen Tajdinian; Mojtaba Jalalpour (Institute of Advanced Engineering and Science, 2014)
In this paper a novel method have been proposed for expansion planning of generation and transmission that considered static security of the system such as voltage security margin And loadability limit. In the same study of expansion planning Security constraints of the system are neglected. In this study at the first step minimum singular value technique is used to evaluate voltage security margin and loadabolity limit, in order to select best bus for load incrimination. After it, in order to Supply the load, coordinated expansion planning of generation and transmission is needed, therefor the strategic interaction between transmission company (TransCo) and generation company (GenCo) for Transmission expansion planning (TEP) and generation expansion planning (GEP) in a competitive electricity market is proposed using Game Theory (GT).DOI:http://dx.doi.org/10.11591/ijece.v4i6.6682